ПРИЧИНЫ ИНТЕРНЕТ-ЗАВИСИМОСТИ У ПОДРОСТКОВ: ОБЗОР ПСИХОЛОГИЧЕСКИХ ИССЛЕДОВАНИЙ - Tatiana GRAUR (Moldova State University, 2018)
В статье рассматриваются проблемы, связанные с установлением причин интернет-зависимости у подростков. Проанализированы психологические исследования, позволяющие выявить в качестве основных причин доступность интернета; низкий уровень цифровой компетентности; возрастные особенности; определенный склад личности; особенности семейных взаимоотношений. THE CAUSES OF INTERNET ADDICTION WITH ADOLESCENTS:  A REVIEW OF PSYCHOLOGICAL RESEARCHES In present article are reviewed the issues related to defining the causes of Internet addiction with adolescents. The psychological researches that allow identifying as the main reasons the following causes: accessibility of Internet; the low level of digital competence; the age peculiarities; the certain personality traits; peculiarities of family relationships.